Implementation of Teaching Factory Vocational School of Center Of Excellence (PK) (Case Study of Learning Aspects of the Culinary and Clothing Expertise Program at SMK Negeri 4 Balikpapan) - Casmudi Casmudi; Sugianto Sugianto; Dinda Tasha Maulida; Hayu Angga H (Budapest International Research and Critics University, 2022)
The background of this research is based on the Government's policy regarding the revitalization of Vocational High Schools, efforts to increase the competitiveness of graduates, so that the target is achieved in the absorption of Vocational High School graduates in the job market. In the absorption of vocational graduates, there is a gap in the implementation of learning in schools that is not yet connected to the competencies needed by the world of work and industry (DUDI). SMK Negeri 4 plays a role as a Center of Excellence (PK) school and has the obligation to organize learning in certain skill programs using Teaching Factory, referring to the guidelines for organizing SMK-PK. The research objectives are to define; (1) implementation of planning, implementation and evaluation (TEFA). (2) Factors supporting or supporting the implementation of TEFA, (3) Obstacles and solutions for the implementation of TEFA. Research methods, using descriptive research with a mixed method approach, collecting data through qualitative dimensions, namely by in-depth interviews, and survey techniques using questionnaires to TEFA actors at SMKN4 Balikpapan. The results of the interviews were analyzed and mapped to draw conclusions to be processed using Atlas-ti software, then coded for the results to be visualized to be displayed and interpreted in the discussion. Research conclusions (1) The implementation of TEFA uses an integrative thematic project based learning model. (2) The supporting factors for the curriculum aspect, teacher human resources, facilities and infrastructure, support from DUDI partners, and the management of TEFA products show good and very good categories. (3) Obstacles and implementation solutions are identified and resolved through a consensus meeting at SMKN 4 Balikpapan.